The bread wheat hardness scenario of the Southern and Western Cape : introducing the particle size index (PSI) method and fourier transform near infrared (FT-NIR) spectroscopy calibrations - Van Zyl, Louise (Stellenbosch : Stellenbosch University, 2012)
Dissertations (M.Sc.Voedselwet.) -- University of Stellenbosch, 1999.